Halal Tourism Opportunities and Challenges in Toraja’s Muslim Minority - Putra, Trisno Wardy; Possumah, Bayu Taufiq; Sikki, Kaisar Lahiya (Universitas Islam Negeri Madura, 2021)
This study describes halal tourism in Muslim minority areas. Halal tourism is an industry currently developing in developed countries, not only in Muslim-majority countries but also in Muslim-minority countries. According to the Global Muslim Travel Index in 2019, Indonesia rose to the top position as a tourist destination. The coronation of Indonesia as the world’s best halal tourism destination is a new wind of optimism for stakeholders in the halal tourism sector. The Ministry of Tourism continues to expand the scope of priority halal tourist destinations. LPPOM MUI, as an institution that focuses on handling halal certification no less agile in conducting halal certification in tourist destinations. However, the development of halal tourism in several areas has been rejected by residents. This study examines the effect of halal tourism and facilities for Muslim tourists visiting Muslim minority areas. The research method used is qualitative by using observation, interviews, documentation, and in the final stage by concluding. This study found that halal tourism in North Toraja was initially rejected due to a lack of socialization in the community. It causes public misunderstanding regarding halal tourism policies. Halal tourism services still need to be improved, from the availability of halal food, worship facilities, water and bathrooms, and religious harmony. Therefore, the development of halal tourism needs to be a concern for the government.